Tratamento da má oclusão de classe II com aparelho Jasper Jumper - Santos-Pinto, Ary dos [UNESP]; Gonçalves, Renata de Cássia [UNESP]; Caldas, Sergei Godeiro Fernandes Rabelo; Martins, Lídia Parsekian [UNESP]; Raveli, Dirceu Barnabé [UNESP] (My University, 2010)
The Jasper Jumper appliance was developed as a fixed orthopedic device that is connected to the upper and lower leveling arches to promote the Class II correction by restricting the maxillary growth (headgear effect), mandibular growth inducement (activator effect) and dentoalveolar changes.

O aparelho Jasper Jumper foi desenvolvido como um dispositivo ortopédico fixo conectado aos arcos de nivelamento superior e inferior visando a correção da Classe II por meio da restrição do crescimento maxilar (efeito extrabucal), estímulo do crescimento mandibular (efeito ativador) e/ou por mudanças dentoalveolares.
Treatment of the class II maloclusion with Jasper Jumper appliance
Keywords: Mandibular advancement; Malocclusion, angle class II; Orthodontic appliances; Avanço mandibular; Maloclusão de angle classe II; Aparelho ortodôntico